Angiopoietin-like 4 : a decade of research - Zhu, Pengcheng (2012)
The past decade has seen a rapid development and increasing recognition of ANGPTL4 (angiopoietin-like 4) as a remarkably multifaceted protein that is involved in many metabolic and non-metabolic conditions. ANGPTL4 has been recognised as a central player in various aspects of energy homoeostasis, at least in part, via the inhibitory interaction between the coiled-coil domain of ANGPTL4 and LPL (lipoprotein lipase). The fibrinogen-like domain of ANGPTL4 interacts and activates specific integrins to facilitate wound healing, modulates vascular permeability, and regulates ROS (reactive oxygen species) level to promote tumorigenesis. The present review summarizes these landmark findings about ANGPTL4 and highlights several important implications for future clinical practice. Importantly, these implications have also raised many questions that are in urgent need of further investigations, particularly the transcription regulation of ANGPTL4 expression, and the post-translation cleavage and modifications of ANGPTL4. The research findings over the past decade have laid the foundation for a better mechanistic understanding of the new scientific discoveries on the diverse roles of ANGPTL4.